1994
DOI: 10.1021/ja00088a083
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Taxoids. Mode of Attachment of the Taxol Side Chain

Abstract: Taxol (1) and taxotere have continued to attract considerable attention because of their promise as agents against various types of cancer (Figure 1). While the threat to the original source of taxol, the Pacific yew, has been diminished as new semisynthetic avenues1 to supply (based upon the availability of 10-deacetylbaccatin III from renewable sources2) have been developed, supply and cost are still major issues. It is anticipated that biosynthetic studies might provide insights which could help alleviate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Floss and associates have conducted a more recent series of illuminating feeding studies with Taxus (Fleming et al, 1993(Fleming et al, , 1994 directed to the sequence of reactions for constructing the 13-O-(N-benzoyl-3-phenylisoserinoyl) side chain; this work is reviewed in Floss and Mocek (1995). These results clearly confirmed that the phenylisoserine side chain is formed from a-phenylalanine via b-phenylalanine.…”
Section: C13-side Chain Assemblymentioning
confidence: 99%
“…Floss and associates have conducted a more recent series of illuminating feeding studies with Taxus (Fleming et al, 1993(Fleming et al, , 1994 directed to the sequence of reactions for constructing the 13-O-(N-benzoyl-3-phenylisoserinoyl) side chain; this work is reviewed in Floss and Mocek (1995). These results clearly confirmed that the phenylisoserine side chain is formed from a-phenylalanine via b-phenylalanine.…”
Section: C13-side Chain Assemblymentioning
confidence: 99%
“…3). After stem wounding in grand fir, the rate of diterpenopid resin biosynthesis increases significantly, but the composition of the rosin products generated differs little from that produced constitutively (Funk et al 1994). After stem wounding in grand fir, the rate of diterpenopid resin biosynthesis increases significantly, but the composition of the rosin products generated differs little from that produced constitutively (Funk et al 1994).…”
Section: Abietanementioning
confidence: 94%
“…Investigations on taxol biosynthesis have shown that acetate, mevalonate, and phenylalanine represent the biosynthetic building blocks of Taxus canadensis taxanes and that the greatest biosynthetic capacity is in the barks (Strobel et al 1992;Zamir et al 1992). It has been shown that baccatin III (XXV) is a precursor of taxol (XXIV), that the side chain is not attached as an intact unit, but most likely as phenylisoserine, and that the final step in biosynthesis is benzoylation ofN-debenzoyltaxol (Fleming et al 1994). Diterpenes 271 shown that the Winterstein's acid [3-(dimethylamino)-3-phenylpropanoic acid] moiety of taxine is derived from phenylalanine (Leete and Bodem 1966).…”
Section: Taxanementioning
confidence: 99%
“…The concentrations of the taxanes in the medium phase, the LA Figure 1. Main biosynthetic pathway of paclitaxel from geranylgeranyl pyrophosphate (GGPP) and the related taxanes [16].…”
Section: Callus Culturementioning
confidence: 99%